2010
DOI: 10.1021/ef100315t
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Studies of Natural Gas Storage with Wet Adsorbents

Abstract: Progress in natural gas storage with wet adsorbents is presented. The storage mechanism switched from adsorption for adsorbed natural gas (ANG) to hydrate formation when wet adsorbents were used. The activated carbon with a pore size of 1.6-3 nm was shown more suitable for the wet storage method, and a larger than 40 wt % gravimetric storage capacity and a deliverable capacity of more than 150 (v/v) were experimentally observed under conditions of 273-283 K and pressure ca. 8 MPa. The stored amount in wet carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…and similar pressure [26,27]. Thus, the storage capacity for methane of carbon sample PY56-8:1 800ºC is similar than the one reached for CNG at 20 MPa, but using half of the pressure.…”
Section: Application: Methane Adsorptionsupporting
confidence: 59%
“…and similar pressure [26,27]. Thus, the storage capacity for methane of carbon sample PY56-8:1 800ºC is similar than the one reached for CNG at 20 MPa, but using half of the pressure.…”
Section: Application: Methane Adsorptionsupporting
confidence: 59%
“…As described along the manuscript, previous studies have anticipated the beneficial effect of water in the methane adsorption capacity of activated carbons [19][20][21] . Although it has been speculated no evidence of methane hydrate formation has been described in the literature up to date.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies reported in the literature have anticipated the beneficial effect of water on methane adsorption, although a deep evaluation of the adsorption process (adsorption kinetics at different steps, phase identification, chemical stoichiometry and so on) and the adsorption mechanism responsible for this behaviour has not been clearly elucidated [19][20][21] . Figure 1b shows the methane adsorption isotherms for heavily water-supplied samples with higher R w ¼ 2.9 and 4.1 (oversaturated samples).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5−10 Zhou et al have reported that using water-wetted carbon can promote the rate of natural gas hydrate formation, reduce the storage pressure, and save costs. 11 −13 In addition, the hydrates are easy to decompose, besides the filling and releasing rates are also improved. However, some problems still need to be studied.…”
Section: Introductionmentioning
confidence: 99%